EXPERT SYSTEM FOR DIAGNOSIS OF KIDNEY DISEASE WITH DEMPSTER SHAFER METHOD AT MEDIKA PLAZA CLINIC - Goldie Gunadi; Adi Nursami (Jurnal Disprotek, 2023)
SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT GINJAL DENGAN METODE DEMPSTER SHAFER PADA KLINIK MEDIKA PLAZACurrent technological advances have changed manual information processing to computerized, making it faster and more accurate. One of the applications of information technology in the health sector is implemented in the form of an expert system application for diagnosing various diseases as done by a doctor or expert. Kidney disease is difficult to detect (often there are no warning signs) but is very life threatening to a person. Kidney is an important organ in the body that performs an important function in the body as a filter for salt, water and acids. The use of expert system applications is expected to provide accurate analytical results in determining the diagnosis of a person's kidney condition. The research was conducted to develop an expert system application for diagnosing kidney disease using the Dempster Shafer method at the Medika Plaza clinic, South Jakarta. From the test results it was concluded that this application could speed up doctors diagnosing patients with symptoms of kidney disease.